Creation Music Pepanggulan Ki Gepang | Tabuh Kreasi Pepanggulan, “Ki Gepang” - Deny Praditya; saptono saptono; I Ketut Partha (GHURNITA: Jurnal Seni Karawitan, 2021)
Ki Gepang is a percussion composition created by pepanggulan using the gamelan Gong Kebyar as a medium of expression. As for the theme raised in this work, namely the sword, the sword that the stylist raised was not just any sword but an heirloom sword left by Manik Angkeran which was used to slash the tail of Naga Basuki in the story of the Selat Bali , which until now is still sacred by the people of Banjar Tegal, Bebalang , Bangli. The stylist's interest in taking up this theme is because the stylist is attracted by the magical and sacred aura of the heirloom and the stylist wants to transform the sharpness, majesty and sacredness of the heirloom into a percussion composition created by pepanggulan. In the musical structure, the stylist uses a tri angga structure, namely pengawit (Head), pengawak (Body), pengecet (Legs) as a basic reference in the stylist's work. And in the creative process, the stylist uses the traditional Balinese method, which in this concept says that there are 3 (three) stages for the process of creating a work of art, namely the conception stage (ngarencana), the execution stage (ngewangun) and ngebah/maedeng.